Older Adults’ Experience of Using Cannabis: Mixed-methods Systematic Review - Seesawang, Junjira; Thongtaeng, Pulawit; Ritthiwong, Tanapa (Nursing Science Journal of Thailand, 2023)
Purpose: To identify and synthesize older adult experiences of using cannabis. Design: A mixed-method systematic review based on PRISMA guideline. Methods: A search for quantitative and qualitative studies published in English or Thai from January 2012 to June 2022 was conducted using Pubmed, CINAHL, PsycInfo, Google Scholar, Sciences direct and ThaiJO databases. Eight studies were found to be relevant and were analyzed using thematic analysis. The findings were synthesized and presented in this review. Main findings: The findings indicated that older adults perceived cannabis use as a legitimate treatment option while some experienced apprehension of public disclosure. Cannabis use was influenced by important reasons for disease management, resulting in the seeking of cannabis from both a license store and a non-license store. The multiple routes of administration for cannabis, such as inhalation and edibles, and its positive and negative effects were reported. The main barrier to cannabis use among older adults is lack of knowledge regarding cannabis. Conclusion and recommendations: This mixed methods systematic review suggests that perceived benefits of cannabis may lead to more cannabis use in older adults. Healthcare providers should monitor cannabis use in older adults and provide accurate information about cannabis, especially focusing on potential dangers of its short-term desired effects. Future research should explore the experience of cannabis use among older adults, such as new users and people who have used it for a long time, to better understand the pattern of usage.